Implementation Creative-Based Learning on Enhancing the Innovative Abilities of Education Students - Li, Mingwei; Mu, Aiwei (Journal of Ecohumanism, 2025)
This paper studies the classroom teaching mode under the category of innovative learning methods to improve the "innovative skills" scores of first-year education students in University. And learning is certainly different from the research of scientists; however, it also requires students to dare to get rid of the old, dare to make new, and dare to explore what they have learned with multiple ways of thinking. This study aims 1) to Use creativity-based learning to enhance the innovation skills of education major students. 2) to Compare the innovation skills of education major students before and after the implementation of creativity-based learning. This study mixed research method of both qualitative and quantitative approaches. An innovative research methodology was adopted, which is a comprehensive innovation project composed of components such as classroom activities, current teaching conditions, innovation topics, and questionnaires. The sample group consists of 100 first-year education major students from Chengdu Normal University in Chengdu, China, who were randomly selected through cluster sampling. The findings that the average score of students before learning training course was 98 points, and after learning training course, it increased to an average of 144 points, with an average difference of 56 points. The results indicate that after learning training course is better. In summary, the study on enhancing the innovative skills of education students through creative based learning demonstrated significant improvements